The performance of 11 fingertip pulse oximeters during hypoxemia in healthy human participants with varied, quantified skin pigmentResearch in context - Gregory Leeb; Isabella Auchus; Tyler Law; Philip Bickler; John Feiner; Shamsudini Hashi; Ellis Monk; Elizabeth Igaga; Michael Bernstein; Yu Celine Chou; Caroline Hughes; Deleree Schornack; et al. (EBioMedicine, 2024)
Summary: Background: Fingertip pulse oximeters are widely available, inexpensive, and commonly used to make clinical decisions in many settings. Device performance is largely unregulated and poorly characterised, especially in people with dark skin pigmentation. Methods: Eleven popular fingertip pulse oximeters were evaluated using the US Food and Drug Administration (FDA) Guidance (2013) and International Organization for Standardization Standards (ISO, 2017) in 34 healthy humans with diverse skin pigmentation utilising a controlled desaturation study with arterial oxygen saturation (SaO 2) plateaus between 70% and 100%. Skin pigmentation was assessed subjectively using a perceived Fitzpatrick Scale (pFP) and objectively using the individual typology angle (ITA) via spectrophotometry at nine anatomical sites. Findings: Five of 11 devices had a root mean square error (ARMS) > 3%, falling outside the acceptable FDA performance range. Nine devices demonstrated worse performance in participants in the darkest skin pigmentation category compared with those in the lightest category. A commonly used subjective skin colour scale frequently miscategorised participants as being darkly pigmented when compared to objective quantification of skin pigment by ITA. Interpretation: Fingertip pulse oximeters have variable performance, frequently not meeting regulatory requirements for clinical use, and occasionally contradicting claims made by manufacturers. Most devices showed a trend toward worse performance in participants with darker skin pigment. Regulatory standards do not adequately account for the impact of skin pigmentation on device performance. We recommend that the pFP and other non-standardised subjective skin colour scales should no longer be used for defining diversity of skin pigmentation. Reliable methods for characterising skin pigmentation to improve diversity and equitable performance of pulse oximeters are needed. Funding: This study was conducted as part of the Open Oximetry Project funded by the Gordon and Betty Moore Foundation, Patrick J McGovern Foundation, and Robert Wood Johnson Foundation. The UCSF Hypoxia Research Laboratory receives funding from multiple industry sponsors to test the sponsors' devices for the purposes of product development and regulatory performance testing. Data in this paper do not include sponsor's study devices. All data were collected from devices procured by the Hypoxia Research Laboratory for the purposes of independent research. No company provided any direct funding for this study, participated in study design or analysis, or was involved in analysing data or writing the manuscript. None of the authors own stock or equity interests in any pulse oximeter companies. Dr Ellis Monk's time utilised for data analysis, reviewing and editing was funded by grant number: DP2MH132941.